Changes in Quality of Life After Secondary Closure of Palatal Defects: Prosthetic Obturation Versus Surgical Reconstruction. Issue 2 (14th March 2022) - Matsumoto, Hiroshi; Ota, Tomoyuki; Takeda, Seiko; Mizukawa, Nobuyoshi; Kimata, Yoshihiro
Abstract : Background: The closure of palatal defects after tumor resection or irradiation is performed with either a prosthesis or autogenous tissue; however, there are no clear criteria regarding selection of the method. Thus, this study aimed to investigate the real-world situation and problems of palatal closure using prostheses, and examined patient opinion on how palatal closure using autogenous tissue improved their postoperative quality of life (QOL). Methods: In 5 patients whose palatal defects resulted from treatment for head and neck cancer and were closed with a prosthesis, the palate was closed secondarily with autogenous tissue; a questionnaire on daily life was administered pre- and post-operatively. Results: Functional improvements in terms of speech and eating were achieved in all and in 4 of 5 cases, respectively. In all cases, the QOL was better for palatal closure with autogenous tissue than with the prosthesis. Conclusions: As postoperative QOL was considered to be better when reconstructing the palate with autogenous tissue than with the prosthesis, we recommend to actively select autogenous tissue for palate reconstruction.